2022
DOI: 10.33448/rsd-v11i6.28671
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Efficiency of the Solar Tracker System compared to the Fixed Solar Generation System

Abstract: Este experimento teve como objetivo analisar o comportamento da diferença de geração entre uma usina fotovoltaica utilizando o sistema de rastreamento solar (Tracker) em comparação com um sistema Fixo voltado ao norte. Ambas as usinas instaladas na região de Cascavel - Paraná. O sistema consiste em duas usinas on-grid de 300kW com 810 módulos de 500wP. No primeiro período de coleta de dados no mês novembro e dezembro 2021, verificou-se que a usina que utiliza o rastreador solar, durante a coleta de dados, alca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Depending on the technology, annual electricity generation of the 1-X tracker is in a range of 1,481-1,644 MWh compared to 1,177-1,377 MWh for the PV with fixed axis, which is 20 to 30 per cent more. This is similar to the previous analysis conducted by Lewandoski et al (2022), in which, to assess the difference in PV generation between PV plants in Brazil, a power plant consisting of two 300 kW on-grid power plants, one with a solar tracking system and the other with a fixed system, was used. They found that the plant that uses the solar tracker, achieved 30% greater generation compared to the fixed plant.…”
Section: Power Generation By Technology and Software Simulationmentioning
confidence: 70%
“…Depending on the technology, annual electricity generation of the 1-X tracker is in a range of 1,481-1,644 MWh compared to 1,177-1,377 MWh for the PV with fixed axis, which is 20 to 30 per cent more. This is similar to the previous analysis conducted by Lewandoski et al (2022), in which, to assess the difference in PV generation between PV plants in Brazil, a power plant consisting of two 300 kW on-grid power plants, one with a solar tracking system and the other with a fixed system, was used. They found that the plant that uses the solar tracker, achieved 30% greater generation compared to the fixed plant.…”
Section: Power Generation By Technology and Software Simulationmentioning
confidence: 70%